2017
DOI: 10.1007/s00520-017-3848-8
|View full text |Cite
|
Sign up to set email alerts
|

Making an informed decision of Korean cancer patients: the discrepancy between a patient’s recall of information and the information needed for acquisition of radiotherapy informed consent

Abstract: Many Korean cancer patients misunderstand the aims of treatment and half of participants do not want further information. Physicians should address whether specific interventions can solve these barriers so that Korean cancer patients can make truly autonomous treatment decisions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 12 publications
1
5
0
Order By: Relevance
“…Nonetheless, according to the results of the word cloud that visualized the opinions of doctors about the decision-making process ( Figure 1 ), doctors expressed that sufficient time should be spent on explanations and that they must communicate with patients to adequately practice shared decision-making, indicating that they recognized what was required without having been educated on shared decision-making specifically. A lack of time and the requests of caregivers were identified as reasons why doctors found it difficult to practice shared decision-making when making decisions about life-sustaining treatment, which is a similar finding to the results of previous studies [ 17 - 19 ].…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…Nonetheless, according to the results of the word cloud that visualized the opinions of doctors about the decision-making process ( Figure 1 ), doctors expressed that sufficient time should be spent on explanations and that they must communicate with patients to adequately practice shared decision-making, indicating that they recognized what was required without having been educated on shared decision-making specifically. A lack of time and the requests of caregivers were identified as reasons why doctors found it difficult to practice shared decision-making when making decisions about life-sustaining treatment, which is a similar finding to the results of previous studies [ 17 - 19 ].…”
Section: Discussionsupporting
confidence: 85%
“…In addition, cancer patients and their caregivers often experience considerable anxiety about information provided to them during the shared decision-making process or experience difficulty accepting information in order to maintain hope. Lastly, a lack of time or issues with the health insurance system can make shared decision-making difficult to practice [ 17 , 18 ]. According to the results of this study, doctors often made decisions about withdrawing life-sustaining treatment without having received sufficient education about shared decision-making (76.2%) and perceived this as a barrier to using practicing shared decision-making when making decisions about life-sustaining treatment ( Table 4 ).…”
Section: Discussionmentioning
confidence: 99%
“…In contrast to this, the level of uncertainty was higher in patients from cohort 2: for 18% of the patients, the treatment goal remained partially unclear and 7% of the patients did not know the treatment goal at all. Subgroup analysis showed that these patients received palliative treatment, which implies communication weaknesses between the treating oncologists and the patients, since full disclosure of a life-threatening diagnosis can be challenging and misconception in cancer communication is a common problem [ 18 ]. Retrospectively, 40% of the patients missed information about alternative therapies.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, a recent article showed that many patients misinterpret the goal of interventions. The framing effect is one of the most powerful factors affecting a patient's decision-making (H. R. Lee, Lim, Yun, Kang, & Kim, 2018). Although the framing effect has been studied in various medical situations, the effect of the word(s) and content in advance directives on individual's decision-making has not been thoroughly evaluated.…”
Section: Discussionmentioning
confidence: 99%